STRATEGI PENGEMBANGAN USAHATANI KOPI UNTUK MENINGKATKAN PRODUKTIVITAS DI DESA AEK SABAON, KECAMATAN MARANCAR, KABUPATEN TAPANULI SELATAN - Pulungan, Syaputra Hidayat (Fakultas Pertanian Universitas Muslim Nusantara Al Washliyah, 2025)
Aek Sabaon Village in Marancar District, South Tapanuli Regency, North Sumatra, has a coffee plantation area of 18 hectares, but its productivity remains low due to high fertilizer prices, pest infestations, and conventional farming techniques. This research aims to analyze the strengths, weaknesses, opportunities, and threats in coffee farming development and formulate strategies to enhance productivity and farmers' welfare. The research employs SWOT analysis to develop coffee farming strategies in Aek Sabaon Village. Internal and external factors are analyzed using the IFAS and EFAS Matrices, which are then used to formulate SO, WO, ST, and WT strategies. The results show an IFAS score of 3.00 and an EFAS score of 3.12, with strengths and opportunities being more dominant than weaknesses and threats. The recommended strategies include optimizing topography, expanding farmland, utilizing infrastructure, digital marketing, international market expansion, and providing training and empowerment programs for farmers to improve productivity and competitiveness.